The three hundred project: The gas disruption of infalling objects in cluster environments - Mostoghiu, Robert (2021)
We analyse the gas content evolution of infalling haloes in cluster environments from THE THREE HUNDRED project, a collection of 324 numerically modelled galaxy clusters. The haloes in our sample were selected within 5R200 of the main cluster halo at z = 0 and have total halo mass M200 ≥ 1011h−1M⊙. We track their main progenitors and study their gas evolution since their crossing into the infall region, which we define as 1–4R200. Studying the radial trends of our populations using both the full phase-space information and a line-of-sight projection, we confirm the Arthur et al. (2019) result and identify a characteristic radius around 1.7R200 in 3D and at R200 in projection at which infalling haloes lose nearly all of the gas prior their infall. Splitting the trends by subhalo status,we show that subhaloes residing in group-mass and low-mass host haloes in the infall region follow similar radial gas-loss trends as their hosts, whereas subhaloes of cluster-mass host haloes are stripped of their gas much further out. Our results show that infalling objects suffer significant gaseous disruption that correlates with time-since-infall, cluster-centric distance, and host mass, and that the gaseous disruption they experience is a combination of subhalo pre-processing and object gas depletion at a radius that behaves like an accretion shock.